Triseptatospora fargesia sp. nov., a bambusicolous ascomycete from Gansu province, China - Wang, Fei-Hu; Liu, Feng; Xiang, Sha-Sha; Xu, Ruo-Lan; Xu, Xiu-Lan; Liu, Ying-Gao; Yang, Chun-Lin (Phytotaxa, 2025)
During a survey of the fungal diversity associated with the primary bamboo species consumed by giant pandas in Gansu Province, China, a unique new species, Triseptatospora fargesia, was discovered. The morphological characteristics of this species include: ascomata that are scattered to gregarious and raised above the surface. Asci that are broadly clavate with short pedicels. Ascospores that are fusiform, 3-septate, and guttulate. These morphological features are similar to the sexual morph characteristics of the genus Triseptatospora. In this study, a phylogenetic analysis was conducted based on the sequence data of the large subunit ribosomal RNA gene (LSU), small subunit ribosomal RNA gene (SSU), and translation elongation factor 1-alpha (tef1-α). The results showed that T. fargesia forms a sister lineage with T. calami within the genus Triseptatospora and represents a distinct species. Morpho-phylogenetic evidence reveals significant differences between Triseptatospora fargesia and Triseptatospora calami. This paper also provides information on the phylogenetic placement and detailed morphological description of this new species.